Birth of a boy after intracytoplasmic sperm injection using ejaculated spermatozoa from a nonmosaic klinefelter syndrome man with normal sperm motility: A case report - Xu, Wen-qing; Yuan, Yuan; Chen, Ying; Luo, Tao; Chen, Hou-yang (Frontiers in Genetics, 2022)
Klinefelter syndrome (KS) is the most common sex chromosome abnormality, which occurs in about one in 660 newly born males, and it is the most common genetic cause of infertility in infertile men, accounting for 11%. It is rare for non-mosaic KS patients to have sperm and reproduce naturally, and there are currently no reports of KS patients with normal motile sperm. Microdissection testicular sperm extraction associated with intracytoplasmic sperm injection (micro-TESE-ICSI) is currently the main assisted reproductive method for patients with KS. In this study, we describe a patient of non-mosaic KS (47, XXY) who had given birth to a healthy girl naturally. The patient had normal male characteristics and did not have the symptoms of hypogonadism commonly seen in KS. He had high levels of serum follicle stimulating hormone and luteinizing hormone, a low level of serum testosterone, and a normal level of prolactin. Semen analysis showed that this case had normal motile sperm (total motility of 57.66 % and progressive motility of 46.19 %) but low sperm concentration (1.7 ×106 cells/mL). He gave birth to a boy by intracytoplasmic sperm injection (ICSI) using his ejaculated sperm purified to high density and motility by Percoll density gradient centrifugation. In conclusion, this case is a unique non-mosaic KS patient who had a normal sperm motility, experienced a natural fertility, and received a successful ICSI outcome, which enlarges our knowledges on non-mosaic KS.